HDAC4 Mediates Smoking-Induced Pancreatic Cancer Metastasis. Issue 2 (February 2022) - Yang, Jiyong; Chheda, Chintan; Lim, Adrian; Hauptschein, Dina; Zayou, Latifa; Tang, Josiah; Pandol, Stephen J.; Edderkaoui, Mouad
Abstract : Objective: Cigarette smoking is an established risk factor for pancreatic ductal adenocarcinoma (PDAC). In this project, we investigated the effect of smoking and the role of histone deacetylase 4 (HDAC4) in PDAC invasion and metastasis. Methods: Cells were treated with 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone and cigarette smoke extract and the mRNA levels of HDACs were measured by real-time polymerase chain reaction. Invasion was measured using the Matrigel Invasion Assay. Syngeneic PDAC mice were treated with 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone and metastasis measured. Human PDAC primary and metastatic tissues were analyzed by immunohistochemistry. Results: Levels of HDAC4 mRNA were increased by smoking. Smoking compounds significantly promoted invasion of cancer cells and promoted metastasis of PDAC cells to different organs, including the liver and the lung, whereas inhibition of HDAC4 prevented this effect. The effect of HDAC4 inhibition on preventing smoking-induced metastasis was greater in the liver compared with the lung. We found that HDAC4 is highly expressed in primary and metastatic PDAC tumors. Conclusions: We found that HDAC4 is the only HDAC induced by smoking among all HDACs analyzed. We found that smoking promotes invasion and metastasis of PDAC cells through a mechanism that involves HDAC4 and that HDAC4 is a promising target for preventing PDAC metastasis.